Does change in cervical dilation after anesthesia impact latency after cerclage placement? - Lende, Michelle N; Feustel, Paul J; Nicasio, Erica K; Lynch, Tara A (Clinical Journal of Obstetrics and Gynecology, 2024)
Background: Pregnant individuals with early cervical dilation have a high risk for preterm birth. The authors encountered cases where cervical dilation increased after anesthesia administration for a cerclage. Objective: The primary objective was to assess if a change in cervical dilation after anesthesia administration for a cerclage was associated with a shorter latency to delivery. Study design: This was a retrospective chart review of pregnancies from January 1, 2011, to December 31, 2021, who had a cerclage and delivered at our institution. Maternal demographics, obstetrical history, operative details, and delivery information were collected. Multi-fetal gestations, un-indicated cerclages, and abdominal cerclages were excluded. The primary outcome was the difference in cervical dilation between the office and the operating room after spinal anesthesia administration. A multivariable regression was performed. Results: A total of 183 pregnancies were included. The mean gestational age at cerclage placement was 18 weeks (STDEV 3.6). Twenty-nine percent of patients (53/183) were more dilated in the operating room compared to the office The latency between cerclage and delivery was not different if there was a cervical change between these settings (p = 0.655). There was an increased risk for preterm delivery with dilation in the office (OR 1.01, CI 1.01 to 2.5), but not with dilation in the operating room (OR 1.4, CI 0.9 to 2.0). Conclusion: Cervical dilation between the office and the operating room is different. Pregnancies with more dilation delivered at earlier gestations. However, a change in dilation between the office and the operating room was not associated with a shorter latency.